PENGARUH PENGOLAHAN TERHADAP KADAR ORYZANOL DAN KOMPOSISI ASAM LEMAK MINYAK BEKATUL DUA VARIETAS PADI LOKAL - Marsono, Yustinus (Jurnal Teknologi Pangan dan Gizi, 2003)
a research on processing of rice bran has been conducted. Two local rice cultivar (Rajalele and Merning) were heated with two heating method i.e. steaming and microwave oven heating. Rice bran were added with water (60% of rice bran weight) and mixed to get semisolid mass. The mass were heated in microwave oven for 5 minutes steamed for 15 minutes and then were extruded and dried in oven at 40-50Â°C. Rice bran oil was extracted from the dry heated rice bran with hexane. The oil was analyzed for oryzanol and fatty acid composition. It was found that rajalele rice bran contain higher fat than the Merning rice bran. Rajalele rice bran oil contains a higher oryzanol than Merning rice bran oil. Steaming and microwave heating decrease the oil and oryzanol content of rice brans. The dominant fatty acids of rice bran oil were olete, lonoleate and palmitate, i.e. 35-44%, 36-42%, and 15-19%, respectively. The process decreased small quantities of unsaturated fatty acids.